Structural and optical properties of SrTiO3 nano material obtained by sol-gel method - Phuong, Doan Thi Thuy; Huy, Nguyen Xuan; Oanh, Le Thi Mai; Bich, Do Danh; Chau, Trieu Thi Minh (Communications in Physics, 2017)
SrTiO3 nano particles were prepared by sol-gel process in order to optimize the temperature condition to obtain good quality material for different applications. The thermal treating condition was selected out through XRD, FTIR and Raman analysis of the synthesized power. The structural and optical property of the powder were studied carefully with XRD, SEM, FTIR, Raman and UV-Vis measurement. At optimized annealing temperature (from 900 oC to 1000 oC), the synthesized STO nano particles have good structure. The shape, size and optical band gap of obtained material are suitable for further applications.